EXPLORING THE DIGITAL AND AI-BASED TRANSFORMATION OF INDONESIAN LOCAL LITERATURE - Kobis, Dewi Christa; Tomatala, Michel Farrel (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2025)
In the era of rapid technological advancement, the transformation of Indonesian local literature through digitalization and artificial intelligence (AI) has become an important cultural phenomenon. This study explores how digital technologies and AI are being utilized to preserve, revitalize, and creatively adapt local literary works rooted in Indonesia’s diverse ethnic and regional traditions. Employing a qualitative library research method, this paper analyzes scholarly literature and digital resources that highlight innovations in multimedia storytelling, language preservation, and AI-generated narratives. The findings indicate that digital platforms such as mobile apps, social media, and webtoons have successfully increased accessibility and cultural relevance of traditional folktales among younger audiences. Furthermore, AI tools like Natural Language Processing (NLP) and generative models have been applied to generate culturally meaningful stories, support language education, and stimulate new creative outputs. However, challenges remain, including issues of authenticity, digital literacy gaps, and limited infrastructure in some regions. This study emphasizes the significant role of technology in shaping the future of local literature, encouraging further collaboration between technologists, educators, and cultural institutions to safeguard and reimagine Indonesia’s literary heritage in the digital age.Key Words: Local Literature, Folktales, Digital Technology, Artificial Intelligence (AI) AbstrakDi era kemajuan teknologi yang pesat, transformasi sastra lokal Indonesia melalui digitalisasi dan kecerdasan buatan (AI) telah menjadi fenomena budaya yang penting. Studi ini mengeksplorasi bagaimana teknologi digital dan AI dimanfaatkan untuk melestarikan, menghidupkan kembali, dan secara kreatif mengadaptasi karya sastra lokal yang berakar pada beragam tradisi etnis dan daerah di Indonesia. Dengan menggunakan metode penelitian pustaka kualitatif, makalah ini menganalisis literatur ilmiah dan sumber digital yang menyoroti inovasi dalam penceritaan multimedia, pelestarian bahasa, dan narasi yang dihasilkan oleh AI. Temuan menunjukkan bahwa platform digital seperti aplikasi seluler, media sosial, dan webtoon telah berhasil meningkatkan aksesibilitas dan relevansi budaya dari cerita rakyat tradisional di kalangan generasi muda. Selain itu, alat AI seperti Natural Language Processing (NLP) dan model generatif telah diterapkan untuk menghasilkan cerita yang bermakna secara budaya, mendukung pendidikan bahasa, dan mendorong lahirnya karya-karya kreatif baru. Namun, masih terdapat berbagai tantangan, termasuk persoalan keaslian, kesenjangan literasi digital, dan keterbatasan infrastruktur di beberapa wilayah. Studi ini menekankan peran penting teknologi dalam membentuk masa depan sastra lokal, serta mendorong kolaborasi lebih lanjut antara teknolog, pendidik, dan lembaga budaya untuk melestarikan sekaligus membayangkan kembali warisan sastra Indonesia di era digital.Kata Kunci: Sastra Lokal, Dongeng, Teknologi Digital, Kecerdasan Buatan